Optimalisasi Teknologi Untuk Akselerasi Implemsentasi Kurikulum - Siska, Jumiati; Mesterjon, Mesterjon; Dewa, Barata Harsena; Cianstury, Irvan; Hamzani, Hamzani (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The Merdeka Mengajar Platform application is a technology platform provided to be a driving companion for teachers and principals in teaching, learning, and working. The Merdeka Mengajar Platform was built to support the implementation of the Merdeka Curriculum so that it can help teachers get references, inspiration, and understanding in implementing the Merdeka Curriculum. The Community Service Team consisting of Lecturers and Students carried out community service activities, especially at the Rejang Lebong Regency Coordinator. Rejang Lebong has not fully understood how to implement the School Mover Program, so the results of observations and interviews from various School Parties, both Elementary and Junior High Schools along with the Education Office conveyed that the problems they are currently facing are the difficulty of learning the PMM (Merdeka Mengajar Platform) and understanding the Pancasila P5 Profile. Thus, the BPMP took the initiative to invite cooperation with Lecturers at the FKIP Dehasen University Bengkulu to support the acceleration of the Implementation of the Merdeka Curriculum in Rejang Lebong. The objectives of this activity are: Providing socialization and training on the use of the Teaching Platform to Junior High School Teachers in Rejang Lebong, Providing socialization and understanding of the Pancasila P5 Profile to Junior High School Teachers in Rejang Lebong. The results of this activity are Community Service Material as additional knowledge for Junior High School Teachers of Rejang Lebong Region II. that it turns out that the use of the Merdeka Mengajar Platform Application is very important. The community service participants were very enthusiastic and excited to participate in the activity, the Pancasila P5 Profile understanders and Junior High School Teachers of Rejang Lebong Region II really felt the effects of the benefits of knowledge about P5.